Distribusi Buku pada Penerbit Prokreatif Media selaku Distributor dalam Menjangkau lebih Banyak Pembaca - Kumala, Anggi; S, Aulia Azmi; Rosari, Hikmah; Amirah, Ummi Afzah; Yusniah, Yusniah (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2023)
This study discusses the distribution of books to procreative media publishers as distributors in reaching more readers. This study aims to find out how the distribution of books to Prokreatif Media publishers as distributors reaches more readers. The research method used in this research is a descriptive qualitative approach. Data collection techniques carried out are by interview and observation. The results of this study indicate that the distribution of books to Prokreatif Media publishers is not only done for profit alone, but to broaden the horizons and knowledge of the Indonesian people by collaborating with many parties such as bookstores, libraries, book fairs, online sales, also cooperate with educational institutions. Prokrasi Media Publisher has succeeded in using several book distribution strategies that are effective in reaching more readers and also being able to spread more goodness and benefits through the books that have been published.